The Impacts of Intention, Academic Stress, and Self-Efficacy on High School Students’ Maladjustment Behaviors - Sartika, Dani; Massuhartono (Universitas Jambi, Indonesia, 2024)
This research aimed to know the influence of intention, academic stress, and self-efficacy on the emergence of maladjustment behavior in high school students from 14 high schools in Jambi City. This research used a quantitative survey approach. The population of this research was high school students in the eleventh grade. In determining sampling, the researcher used the G*Power application to analyze the strength of the sample. The instrument used three scales, consisting of the psychological well-being scale, Peer’s Perceived Support Scale (PPSS), and the General Self-Efficacy Scale (GSE). In data analysis, the research used Double Linear Regression (DLR). The research results showed acquisition coefficient R=0.742 and F=59,404 (p<0.001). Overall, the conclusion is that, simultaneously, there was an influence that is incredibly significant between intention, academic stress, and self-efficacy on maladjustment behavior.